Implementasi dan Akibat Hukum Perjanjian Perkawinan Setelah Keluarnya Putusan MK NO.69/PUU-XIIX/2015 - Suhaila Zulkifli (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
AbstractThe marriage agreement is marriage planning, and each couple is entitled to prepare it. The marriage agreement serves is a preparation for living a home life to minimize and to avoid a dispute between husband and wife, and to provide legal certainty between the rights and obligations of each party. In the Marriage Law No. 1 of 1974, Article 29 Paragraph (1) states that the Marriage Agreement must be executed when or before the marriage takes place; by the enactment of the Constitutional Court Decision No. 69 / PUU-XIII / 2015, the phrase "when or before marriage takes place" is now changed that the Marriage Agreement may be executed after the marriage takes place during the marriage bond. The legal consequence of the issuance of the Constitutional Court's decision is more legal protection especially for women not to become victims of domestic violence, guaranteeing the protection of property rights or building rights of the property so that the spouse focuses on marriage destination. Keywords: Implementation, legal effect, Marriage Agreement